Diterminasi Peningkatan Kinerja Pegawai Dinas Perikanan Kota Pasuruan - Fera Mustika, Dini Firdaus; Maharini, Dewi; Syafitri, Helisda; Suindyah Dwiningwarni, Sayekti (MES Bogor, 2025)
The purpose of this study is to analyze the effect of Training, Soft skills and Career Paths on Performance through Job Satisfaction at the Pasuruan City Fisheries Service. The study uses a quantitative approach with a causal research plan at the Pasuruan City Fisheries Service. The sampling method uses a Purposive Sampling technique with the criteria a) Having worked for at least 6 months and b) Knowing the work process at the Pasuruan City Fisheries Service. Therefore, the sample taken in this study was 33 employees of the Pasuruan City Government Agriculture and Food Security Service. The data collection technique was through a questionnaire and analyzed through Partial Least Square analysis. The results of the study prove that training, soft skills, and career ladder have a significant positive effect on job satisfaction at the Pasuruan City Fisheries Service. Training and job satisfaction have a significant positive effect on performance at the Pasuruan City Fisheries Service. However, soft skills and career ladder do not have a significant positive effect on performance at the Pasuruan City Fisheries Service. Job satisfaction is able to mediate the relationship between training, soft skills, and career ladder on performance at the Pasuruan City Fisheries Service.